2017
DOI: 10.1038/ni.3755
|View full text |Cite|
|
Sign up to set email alerts
|

The microRNA miR-31 inhibits CD8+ T cell function in chronic viral infection

Abstract: During infection, antigen-specific T cells undergo tightly regulated developmental transitions controlled by transcriptional and post-transcriptional regulation of gene expression. We found that the microRNA miR-31 was strongly induced by activation of the T cell antigen receptor (TCR) in a pathway involving calcium and activation of the transcription factor NFAT. During chronic infection with lymphocytic choriomeningitis virus (LCMV) clone 13, miR-31-deficent mice recovered from clinical disease, while wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 65 publications
(75 reference statements)
2
62
0
Order By: Relevance
“…Although MIR31HG outlier profiles were shown to be both cancer‐specific and cancer cell‐intrinsic, we cannot exclude the possibility that the noncancerous tumor compartment may contribute to MIR31HG expression in some cases. Recently, it was shown that miR‐31‐5p expression in T cells increased during exposure to type I interferons . However, our analyses indicated that the prognostic value of MIR31 was independent of the level of CTL infiltration, and combination of the two markers identified a patient subgroup with a particularly poor survival.…”
Section: Discussionmentioning
confidence: 55%
“…Although MIR31HG outlier profiles were shown to be both cancer‐specific and cancer cell‐intrinsic, we cannot exclude the possibility that the noncancerous tumor compartment may contribute to MIR31HG expression in some cases. Recently, it was shown that miR‐31‐5p expression in T cells increased during exposure to type I interferons . However, our analyses indicated that the prognostic value of MIR31 was independent of the level of CTL infiltration, and combination of the two markers identified a patient subgroup with a particularly poor survival.…”
Section: Discussionmentioning
confidence: 55%
“…As a result, miRNAs can have diverse effects based on the cell type and cell state examined (Lu et al, 2015). Although there has been considerable effort to understand the role of specific miRNAs in the immune system and, to a lesser extent, in T cells (Moffett et al, 2017), there is little information about the role of specific miRs in T EX cells.…”
Section: Introductionmentioning
confidence: 99%
“…Through decades of investigations, thousands of miRNAs have been found in humans and animals, among which a notable proportion of miRNAs are found to be critical in the pathogenesis of various diseases, including cardiovascular diseases [9,10,11,12,13,14]. Moreover, some circulating miRNAs predominantly express in CAD patients [15,16].…”
Section: Introductionmentioning
confidence: 99%